A Set of Methods for the Formation of Vocal Skills in Preschool Children - Маллабоев Авазбек Ганижонович (Peerian Journals Publishing, 2022)
All vocal skills are closely interrelated, so work on them should be carried out in parallel. Naturally, each vocal exercise has the goal of forming some definite skills, but when performing it, it is impossible to let the rest out of the attention. This is the main difficulty for a little singer - to learn that in order to achieve a sustainable result, it is necessary to use absolutely all the knowledge, skills and abilities acquired in the classroom.
Keywords: variety art; teaching method; comparison; singer